How to strengthen primary health care? An exploratory study on the policy of vertical integration of high-quality medical resources based on symbiosis theory - Zhao, Linyan; Du, Jie; Liu, Wenhao; Xu, Qun; Zhang, Yuhui (Frontiers in Public Health, 2025)
BackgroundThe Vertical Integration of High-Quality Medical Resources (VI-HQMR) is a strategy of medical resource reallocation. It is the key to strengthen primary health care (PHC) and build an integrated delivery system (IDS). It contributes to the Sustainable Development Goals (SDGs) of universal health coverage (UHC) set out by the World Health Organization (WHO). In order to VI-HQMR, countries around the world have carried out many beneficial explorations. However, our understanding of the importance of clarifying the internal logical from policy perspective in the VI-HQMR is limited. This study aims to develop a theoretical model from the symbiotic perspective to improve the strategy of VI-HQMR.MethodsPolicies related to the VI-HQMR were retrieved for exploratory research. The texts and entries were coded according to the four elements of symbiosis theory, the first-level categories and their variables were mined, and the occurrence frequency was used as the main indicator for thematic clustering.ResultsA total of 609 policies were retrieved, among which 1,072 entries mentioned VI-HQMR. Results showed that the VI-HQMR included 482 symbiotic units, 549 symbiotic models, 383 symbiotic environments and 96 symbiotic interfaces. Secondary and above public hospitals and PHC institutions are the most important symbiotic units. Medical alliances are the most important symbiotic model. The symbiotic environment includes policy, technology and economics. The vertical integration of human resources is the main symbiotic interface.ConclusionThe VI-HQMR is still in the initial exploration stage. The symbiotic model is changing from parasitism to the commensalism. To achieve the optimal mutualism model, we need to work hard from the symbiotic environment. Health administrative department should coordinate with other relevant departments to introduce special policies to support the VI-HQMR. Through opening the way for promotion, financial incentive, and informationization assistance, improve the enthusiasm of urban hospitals.